1997
DOI: 10.1785/bssa0870020356
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ground-motion intensity inferred from questionnaire survey, earthquake recordings, and microtremor measurements—A case study in Christchurch, New Zealand, during the 1994 arthurs pass earthquake

Abstract: The areal distribution of seismic ground-motion intensity in the city of Christchurch, New Zealand, during the 1994 Arthurs Pass Earthquake (ML 6.6) was evaluated using an intensity questionnaire together with local site amplifications inferred from seismic recordings and microtremors. In order to estimate the intensity in parts of the city where no intensity data were available, intensity data were compared to relative levels of shaking determined from both weak-motion and microtremor recordings. Weak ground-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…These 12-min-long records were collected using a Micromed Tromino at a sampling frequency of 128 Hz. Mucciarelli (2011) observed mHVSR periods ranging from 0.15 to 1.0 s, which agree with the observations of Toshinawa et al (1997). A general trend of decreasing period moving westward across the city was noted.…”
Section: Microtremor Datasets In the Canterbury Regionsupporting
confidence: 86%
See 3 more Smart Citations
“…These 12-min-long records were collected using a Micromed Tromino at a sampling frequency of 128 Hz. Mucciarelli (2011) observed mHVSR periods ranging from 0.15 to 1.0 s, which agree with the observations of Toshinawa et al (1997). A general trend of decreasing period moving westward across the city was noted.…”
Section: Microtremor Datasets In the Canterbury Regionsupporting
confidence: 86%
“…The previous mHVSR studies (Mucciarelli, 2011; Toshinawa et al, 1997) reported site periods ranging from 0.2 to 1.0 s. Due to short time records or the limitations of instrumentation used, the long-period response of the deep basement was not identified. Thus, the reported periods likely correspond to either the period above the Riccarton Gravel or the BPV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations